Dominacja paradygmatów czy też wyjaśnień komplementarnych w okresie zmiany społecznej? = Domination of paradigms or complimentary explanations in the era of social change? - Radziewicz-Winnicki, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Social paradigms exists, in the tradition of social sciences, as narrow theoretical and research fields, but they hope to expand beyond their original scope leading to scientific recognition. The author analyzes the nature of paradigms and their usefulness in the era of social change. In final part of the article, the author comes to the conclusion that social sciences researchers should use complimentary explanations instead of applying traditional paradigms.
Keywords: zmiana społeczna; paradygmat; nauki społeczne